2014
DOI: 10.1093/annonc/mdt535
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib dose-escalation study of everolimus combined with cisplatin and etoposide as first-line therapy in patients with extensive-stage small-cell lung cancer

Abstract: Everolimus 2.5 mg/day plus G-CSF was the only feasible dose given with standard-dose EP in untreated extensive-stage SCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…While previous clinical trials with mTOR inhibitors in SCLC have not shown favorable outcomes, patients in those studies were not stratified on the basis of MYC status (28)(29)(30). On the basis of our findings, it is possible that selecting patients based on expression of MYC family members may improve outcomes in the clinic.…”
Section: Myc-driven Human Sclc Is Preferentially Sensitive To Argininmentioning
confidence: 84%
See 1 more Smart Citation
“…While previous clinical trials with mTOR inhibitors in SCLC have not shown favorable outcomes, patients in those studies were not stratified on the basis of MYC status (28)(29)(30). On the basis of our findings, it is possible that selecting patients based on expression of MYC family members may improve outcomes in the clinic.…”
Section: Myc-driven Human Sclc Is Preferentially Sensitive To Argininmentioning
confidence: 84%
“…mTOR inhibitors in combination with either BCL2 inhibitors, BH3 mimetics, or chemotherapy have shown efficacy in SCLC cell lines and xenografts, although these studies did not evaluate MYC status or the chemo-resistant setting (25)(26)(27). In SCLC clinical trials, mTOR inhibitors did not demonstrate a significant improvement in outcome either in the first-line setting combined with chemotherapy or in the second-line setting as a monotherapy (28)(29)(30). However, these studies did not determine whether MYC status could stratify patient response.…”
Section: Introductionmentioning
confidence: 98%
“…Based on the evidence from pivotal data the consensus was to start with the labeled dose of 10 mg and de-escalate if necessary. [20] This is supported by the study in metastatic renal cell carcinoma that predicted median change in single largest diameter (SLD) of the disease will be increase of 22.4 ± 17.2% with 5 mg of Everolimus and reduction of 15.7 ± 11.5% with 10 mg. [21] For frail patients a fraction of oncologists may still continue to start with a lower dose and escalate if no toxicity, but this is without evidence and not recommended. [22] Measures to prevent and minimize toxicity used in clinical trials are often neglected in routine clinical practice.…”
Section: Role Of Everolimus Refined [Table 19]mentioning
confidence: 86%
“…Cisplatin (cis-diamminedichloroplatinumⅡ, CDDP) is one of the main chemotherapeutics, which is widely used for the treatment of various malignant solid tumors such as ovarian, lung, testicular and head and neck cancers (Pfister et al, 2010;Dimri et al, 2013; Dua et al, 2013;Besse et al, 2014 …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the effectiveness and feasibility of chemotherapy for cancers species involving the lung, pancreas, liver, large intestine, and so on. Conversely, treatment with anticancer drugs can also do harm to patients' normal tissues and organs, and those toxicities may lead to a worsened quality of life and shortened survival.Cisplatin (cis-diamminedichloroplatinumⅡ, CDDP) is one of the main chemotherapeutics, which is widely used for the treatment of various malignant solid tumors such as ovarian, lung, testicular and head and neck cancers (Pfister et al, 2010;Dimri et al, 2013; Dua et al, 2013;Besse et al, 2014 …”
mentioning
confidence: 99%